2006
DOI: 10.1128/aem.00855-06
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Expression of Respiratory Genes in an Enrichment Culture Containing Dehalococcoides ethenogenes

Abstract: Multiple reductive dehalogenase (RDase), hydrogenase (H 2 ase), and other respiration-associated (RA) oxidoreductase genes have been identified in cultured representatives of Dehalococcoides. Although their products are likely to play key roles in the environmentally important process of reductive dechlorination, very little information is available about their regulation and specific functions. Here we show increased expression and temporal variability in the expression of five RDase genes and in the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(124 citation statements)
references
References 20 publications
(28 reference statements)
11
111
2
Order By: Relevance
“…The dceA7 gene (100% identity to DET0088) is truncated, and the 3 0 anchoring protein is replaced by a hypothetical protein. Nevertheless, recent studies have reported that the expression of DET0088 was upregulated during PCE dechlorination in Alameda Naval Air Station enrichments and mixed cultures containing strain 195 (Rahm et al, 2006;West et al, 2008). Also, the dceA7 gene was identified using the newly designed primer pairs, RDH F1C and RDH R1C, revealing inadequacies of the previous degenerate primer pair.…”
Section: Discussionmentioning
confidence: 99%
“…The dceA7 gene (100% identity to DET0088) is truncated, and the 3 0 anchoring protein is replaced by a hypothetical protein. Nevertheless, recent studies have reported that the expression of DET0088 was upregulated during PCE dechlorination in Alameda Naval Air Station enrichments and mixed cultures containing strain 195 (Rahm et al, 2006;West et al, 2008). Also, the dceA7 gene was identified using the newly designed primer pairs, RDH F1C and RDH R1C, revealing inadequacies of the previous degenerate primer pair.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with trichloroethene (TCE)-and tetrachloroethene (PCE)-grown cells of strain 195 indicated that the genes encoding the PCE and TCE reductive dehalogenases (PceA, TceA) were transcribed to the highest levels among all 17 rdhA genes [25], and the corresponding proteins were identified with a high coverage in the proteome of the respective cells [26]. Furthermore, rdhA gene expression levels depended on the growth phase and the PCE respiration rate [27][28][29]. Consequently, they were used as biomarkers for active PCE or TCE dechlorination in technical and groundwater systems [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…This genus, although phylogenetically distant to Dehalobacter, inhabits similar ecological niches, and is exclusively dependent on OHR metabolism with H 2 as electron donor. These studies have used both transcriptomics using full genome microarrays and proteomics to identify key components of the metabolism of OHRB under different growth conditions or growth phases [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%